Differences in Perceptions of Learning Environment Between Achievers and Underachievers in Medical College Sebelas Maret University - BENAZIER MARCELLA BESMAYA; Ari Natalia Probandari; Amandha Boy Timor Randita (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: The presence of underachievers becomes a problem for both parents and educators due to waste the potential which is not only the loss of the nation, but also a personal loss to such individual to excel. The learning environment is one of the factors that affect the academic performance of students. It determines students perception and is important to reveal aspects of the learning environment that needs to be evaluated in order to maximize the academic performance of students. Methods: This was a descriptive analytic study with a cross-sectional design and held at the Faculty of Medicine, Sebelas Maret University. This study was using a validated The Dundee Ready Educational Environment Measure (DREEM) and was administered to 192 students of 4th year Medical College Sebelas Maret University. The data was analyzed by unpaired t-test and Mann-Whitney test (? = 0.05). Results: The perception of both achievers and underachievers was more positive than negative (average scores 81.62 and 80.00 out of 132). There were no significant differences between the two groups on total or subscale score. There were significant differences on problem solving skill between the two groups (p<0.05). There were some items indicating as problem areas and thus required remedial steps. Conclusion: Both achievers and underachievers in Medical College Sebelas Maret University assess the learning environment as more positive than negative. There are no significant differences in the perception of learning environments between achievers and underachievers (p> 0.05). Keywords: learning environment, perception, achiever, underachiever, DREEM